Kepatuhan Wajib Pajak dalam Penyampaian SPT: Analisis Kasus Pengemplangan Pajak di PN Semarang - Tiara Aurelia Shafira; Sulistari Sulistari; Madina Lintang Tsalatsa; Regina Ratri Azizah Pratiwi (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Taxes are the primary source of state revenue and play an essential role in financing national development. Indonesia’s taxation system adopts a self-assessment system, under which taxpayers are entrusted with calculating, paying, and reporting their tax obligations through the Tax Return (SPT). However, in practice, violations such as late filing, inaccurate reporting, and failure to submit tax returns are still frequently found, potentially causing losses to state revenue. This study aims to analyze the regulations governing tax return submission within Indonesia’s taxation system and the legal implications of incorrect tax return submissions based on the Decision of the Semarang District Court Number 608/Pid.Sus/2025/PN Smg. This study employs a normative legal research method using statutory and case approaches. Legal materials were collected through library research and document analysis and were subsequently analyzed qualitatively. The results indicate that tax return submission is regulated under the General Provisions and Tax Procedures Law, which requires tax returns to be completed correctly, comprehensively, and clearly. Violations involving intentional conduct and causing state financial losses may result in criminal sanctions as an ultimum remedium. The case examined demonstrates that tax return submission is not merely an administrative obligation but also carries legal consequences to maintain taxpayer compliance and state revenue.